Perlindungan Hukum Hak Cipta Lagu/Musik atas Royalti dalam Perspektif Teori Keadilan Menurut Undang-Undang No. 28 Tahun 2014 Tentang Hak Cipta - Ramadani, Muhammad Aru; H, Hartana; Setiawan, Puguh Aji Hari (Media Hukum Indonesia (MHI), 2025)
This article examines the legal protection of copyright in songs and music, particularly in relation to the royalty payment system regulated by Law No. 28 of 2014 on Copyright. Royalties for the commercial use of music are a crucial issue in the protection of intellectual property rights, especially the economic rights of creators. The study employs a normative juridical approach, analyzing positive law and conceptual perspectives using John Rawls's and Gustav Radbruch’s theories of justice. The findings reveal that although legal norms exist, their implementation does not yet reflect ideal justice. Therefore, reformulating a justice-based copyright protection system is essential to ensure the fair treatment of songwriters and composers.